2019
DOI: 10.1111/flan.12380
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to learn languages other than English: A critical research synthesis

Abstract: The primary purpose of this investigation was to put forward critical research synthesis as a qualitative alternative to meta‐analysis in second language acquisition using as a case example studies published from 2005 to 2018 applying the L2 Motivational Self System (L2MSS) to learners of languages other than English (LOTEs). Since L2MSS research is methodologically diverse and meta‐analysis necessarily excludes literature that cannot be subjected to its parameters, a qualitative synthetic approach with the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 69 publications
1
34
0
4
Order By: Relevance
“…There is growing concern that learners may lose interest in learning a LOTE in the age of English globalization and in the current populist climate (Busse, 2017; Lanvers, Doughty, & Thompson, 2018). Although language‐learning motivation research is vibrant, an overwhelming majority of empirical research has focused on motivation to learn global English (Boo, Dörnyei, & Ryan, 2015), and only around a quarter of the studies include LOTEs (Mendoza & Phung, 2019). Researchers have recently begun to resituate language‐learning motivation in the LOTE setting (see Ushioda & Dörnyei, 2017), but only a few studies have integrated motivation and multilingualism (e.g., Busse, 2017; Csizér & Lukács, 2010; Henry, 2011, 2017; Henry & Thorsen, 2018; Thompson, 2017b; Zheng, Lu, & Ren, 2019), and these were mainly conducted in European and Anglophone contexts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing concern that learners may lose interest in learning a LOTE in the age of English globalization and in the current populist climate (Busse, 2017; Lanvers, Doughty, & Thompson, 2018). Although language‐learning motivation research is vibrant, an overwhelming majority of empirical research has focused on motivation to learn global English (Boo, Dörnyei, & Ryan, 2015), and only around a quarter of the studies include LOTEs (Mendoza & Phung, 2019). Researchers have recently begun to resituate language‐learning motivation in the LOTE setting (see Ushioda & Dörnyei, 2017), but only a few studies have integrated motivation and multilingualism (e.g., Busse, 2017; Csizér & Lukács, 2010; Henry, 2011, 2017; Henry & Thorsen, 2018; Thompson, 2017b; Zheng, Lu, & Ren, 2019), and these were mainly conducted in European and Anglophone contexts.…”
mentioning
confidence: 99%
“…The notion of motivation as a static and fixed attribute has gradually been replaced by a dynamic, fluid view (Dörnyei, MacIntyre, & Henry, 2015). Despite the surge in interest, longitudinal empirical studies are still in a minority in the language‐learning motivation literature (Boo et al., 2015; Mendoza & Phung, 2019). Recent developments in L2 motivation research have advanced a complex dynamic systems theory (CDST) perspective to address the situated and dynamic nature of motivation (Henry, 2017; Hiver & Larsen–Freeman, 2020; Hiver & Papi, 2020; Papi & Hiver, 2020; Thompson, 2017b).…”
mentioning
confidence: 99%
“…Where these options are more likely to provide students with a meaningful volume of language study (one that could be relevant to employability), questions about the motivations for language study, as well as the form and volume that study takes to also support employability learning, must be considered. In European, Asian and American contexts, knowledge of another language is often perceived as an 'added value' (Heller & Duchêne, 2012, p. 2) as it enriches a person's economic, academic and symbolic capital (Kramsch, 2014;Mendoza & Phung, 2019). This valuing of languages, including in relation to employability, has nonetheless led to a differentiated ranking of languages (Heller & Duchêne, 2012) with English being a sought-after employment-related skill for non-native English speakers (Thompson, 2017).…”
Section: Factors That Influence Students To Study Languagesmentioning
confidence: 99%
“…In response to the gap in research, a recent issue of the Modern Language Journal (2017, 101.3) examined motivation in the context of learning Languages Other Than English (LOTEs). Similarly, in the Foreign Language Annals, Mendoza and Phung (2019) analyzed the status of research into L2/LOTE motivation and found it lacking.…”
Section: Motivation Researchmentioning
confidence: 99%
“…At the onset, one needs to note that if the situation for motivation research in LOTEs is generally dire, it is particularly so for the study of German in a university context. Mendoza and Phung (2019) identified only three such studies: Busse (2013) in the U.K., Huang, Hsu, and Chen (2015) in Taiwan, and Okuniewski (2014) in Poland. Okuniewski's study encompassed theoretical concepts from both the AMTB and L2MSS.…”
Section: Motivation Researchmentioning
confidence: 99%